New scaling of bracketing method for fourth and sixth section / Nur Aizat Noor Manshah & Nurhidayatul Liyana Mohd Mustafa - Noor Manshah, Nur Aizat; Mohd Mustafa, Nurhidayatul Liyana (2019)
Numerical analysis is widely used in mathematical area for solving root of nonlinear functions. Bracketing Method is the easiest numerical method for root finding and some of the methods are Fourth Section and Sixth Section. In this research, Fourth and Sixth Section are modified by adding a scalar in order to solve for the nonlinear functions. These nonlinear functions are being analysed for their efficiency in terms of number of iteration and CPU times by using the methods mentioned above. The approximation roots for these methods are compared with the actual roots to acquire for their accuracy.